2019
DOI: 10.1186/s40634-019-0204-6
|View full text |Cite
|
Sign up to set email alerts
|

Tapentadol vs oxycodone/naloxone in the management of pain after total hip arthroplasty in the fast track setting: an observational study

Abstract: Background In recent years, joint replacement surgery has gradually progressed towards the fast-track model, and early rehabilitation immediately after surgery is regarded fundamental for optimal recovery of function: the aim of the present study is to describe the efficacy in perioperative management of pain in patients undergoing total hip replacement surgery and treated with tapentadol or oxycodone/naloxone in combination with ketoprofene. Methods Single-center retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In this study, no case of intestinal obstruction was observed. Some scholars reported that the incidence of acute colonic pseudoobstruction after hip and knee replacement was 1.3% and 0.65%, respectively [12][13][14][15]. Postoperative bowel Arthroscopic minimally invasive surgery is a surgery performed using an arthroscope and its related instruments, which is an important part of modern surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no case of intestinal obstruction was observed. Some scholars reported that the incidence of acute colonic pseudoobstruction after hip and knee replacement was 1.3% and 0.65%, respectively [12][13][14][15]. Postoperative bowel Arthroscopic minimally invasive surgery is a surgery performed using an arthroscope and its related instruments, which is an important part of modern surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in LBP patients suggests that the combination therapy (tapentadol PR + pregabalin) exerts its best clinical efficacy in subjects characterized by severe sleep disturbances and little anxiety [72]. Moreover, a study by D'Amato et al showed the efficacy of the combination of tapentadol and ketoprofen after hip arthroplasty [73]. The combination with other analgesics allows to reduce the dosage of tapentadol, although further dedicated studies on this treatment approach are required, since data obtained to date are not fully positive.…”
Section: Chronic Back Painmentioning
confidence: 99%
“…Although less intriguing, the same concept of combining more elements to improve the outcome is common to many fields of human activity, including medicine. Let's think of drugs combining diuretics and angiotensin-converting enzyme inhibitors to increase the antihypertensive effect, or pain killers associating paracetamol to opioids or opioids to their receptor antagonist 1 : nothing unusual for practitioners of several medical specialties. Even in the field of injectables for osteoarthritis, we may recall products combining hyaluronic acid (HA) and corticosteroids for intra-articular use 2 : the obvious rationale is to take advantage of the simultaneous administration of different molecules with complementary mechanisms of action.…”
Section: See Related Article On Page 903mentioning
confidence: 99%